Confinement effects of ion tracks in ultrathin polymer films - Papaléo, R. M. (2015)
We show direct experimental evidence that radiation effects produced by single MeV heavy ions on a polymer surface are weakened when the length of the ion track in the material is confined into layers of a few tens of nanometers. Deviation from the bulk (thick film) behavior of ion-induced craters starts at a critical thickness as large as ∼40nm, due to suppression of long-range additive effects of excited atoms along the track. Good agreement was found between the experimental results, molecular dynamic simulations, and an analytical model.